PENGARUH SARANA PRASARANA, KEMAMPUAN PENGGUNA, SOSIALISASI, DAN PENGAWASAN TERHADAP EFEKTIVITAS PENERAPAN SISTEM INFORMASI PEMERINTAH DAERAH (SIPD) BAGI PENGELOLA KEUANGAN DI PEMERINTAH KOTA PAYAKUMBUH - Putri, Yellita Eka; Zuripal, Zuripal (Jurnal Manajemen, 2024)
This study aims to analyze the influence of infrastructure, user capability, socialization, and supervision on the effectiveness of the implementation of the Regional Government Information System (SIPD). The population in this study was the Expenditure Treasurer and Assistant Expenditure Treasurer of Payakumbuh City. This study uses a quantitative method with primary data in the form of questionnaires with a sample size of 195 respondents taken based on saturated sampling technique. The data analysis technique used is descriptive analysis and inferential statistical analysis with Structural Equation Modeling (SEM) of various Partial Least Squares (PLS) variants. Measurement model or outer model, structural model or inner model testing, and hypothesis testing with the help of Smart-PLS 4.0 software as a testing tool. The results showed that the availability of infrastructure, user capability, and supervision significantly influenced the effectiveness of SIPD implementation. However, socialization did not show a significant influence. This study concludes that to improve the effectiveness of SIPD, there needs to be an improvement in the quality of infrastructure, more intensive training for users, and better supervision mechanisms.